The correlation of body mass index with clinical factors in patients with first-episode depression - Jieqiong, Hu; Yunxin, Ji; Ni, Dai; Chen, Lin; Ying, Chai (Frontiers in Psychiatry, 2022)
Depression is one of the major disease burdens worldwide. Few studies have addressed body mass index in Chinese depression patients. This current study aimed to investigate the body mass index in patients with depression and the correlation with clinical factors. A total of 211 inpatients with first-episode depression were enrolled. General and clinical data were collected by standardized questionnaires and the levels of hemoglobin, fasting blood glucose, uric acid and blood lipid were measured. 24-item Hamilton Depression Scale (HAMD) and 14-item Hamilton Anxiety Scale (HAMA) were rated for all patients. The BMI of 211 patients with depression was 37 (17.5%) in the underweight group, 117 (55.5%) in the normal-weight group, 43 (20.4%) in the overweight group, and 14 (6.6%) in the obesity group.  Multivariate Logistic analysis showed that uric acid was the only risk factor for BMI. The ordered logit model showed that the risk of elevated uric acid increased with BMI grade. And the risk of severe depression was significantly greater in pantients with underweight than those in normal-weight. The level of uric acid in patients with first-episode depression is positively correlated with BMI, and the score of depressive symptoms is higher in patients with underweight.